Patrones de asentamiento del Malpaís de Zacapu (Michoacán, México) y de sus alrededores en el Posclásico - Migeon, Gerald, (Paris monographs in American archaeology ;, 2016)
This volume presents the results of the archaeological studies relative to the settlement pattern, realised within the framework of the Michoacán Projects I and III, studying of all the perceptible demonstrations of the prehispanic occupations in the region.